CHANGE YOUR WORLD : HOW ANYONE, ANYWHERE CAN MAKE A DIFFERENCE - Maxwell, John C., 1947-; Hoskins, Rob (Nashville, United States : HarperCollins Leadership, 2020)
John Maxwell and Rob Hoskins have invested their lives as champions of change. Maxwell's organizations EQUIP and the John Maxwell Leadership Foundation have transformed communities by training more than five million leaders from literally every country in the world. Hoskins's One Hope has transformed the lives of more than one billion children and youth in 120 countries around the globe. Now, for the first time, these two leaders have partnered to write a book about how anyone, anywhere, can transform their world. Offering practical principles based on solid research and real-life experience, the authors teach how to recognize where and how to get started, who to recruit, when to mobilize people, what to do, how to communicate, and how to know when they've really hit the target. This accompanying workbook integrates the power of Maxwell's familiar and engaging leadership communication with the research-based international insights of Hoskins's and One Hope global experience. Transformation is within the reach of anyone who is willing to think, speak, and act in a way that values people and collaborates with them to bring about lasting positive change. This workbook will give them the tools to go through the steps, based on the trade book, to make that happen in their lives.
Bibliography: pages 210-226
Keywords: Leadership; Decision making; Strategy; Social change